Production of Persimmon Juice with Technology Ultrafiltration of Membrane to Improve People's Skills - Rengga, Wara Dyah Pita; Siami, Desy Hikmatul; Nabil, Nisrina Hasna'; Handoko, Pratama Senapati Bagus; Pangestu, Indra Sakti; Saputra, Danang Dwi; Hidayah, Fauziyah Nurul (Rekayasa : Jurnal Penerapan Teknologi dan Pembelajaran, 2022)
COVID-19 impacted the Grabag Village community's economic instability, resulting in the termination of employment. Grabag Village has the potential for persimmons as fresh fruit consumption, which lasts only less than two weeks. It is the background for the community empowerment activities for three months. The program aims to utilize membrane ultrafiltration technology and introduce the use of chitosan preservatives to the community. The implementation method applied includes the preparation, implementation, and evaluation stages. The results of this activity program show an increase in the knowledge of the partner community regarding the basic introduction of persimmon fruit, diversification of persimmon fruit products, and understanding of the production process with an average value of above 80%. However, only 75% of all partners understand online marketing from a technological point of view. Community assistance is needed to face the challenges of digitizing business actors to expand market share and reach increasingly widespread smartphone users. The community knows the potential of persimmon fruit, which can be used to make many processed products into ready-to-drink drinks. The partner also knows chitosan as a natural preservative and practices adding it directly to fruit juice, packaging, and labelling. After the socialization stage, the community is more educated regarding the procedures for making ready-to-sell persimmon juice from persimmon fruit.